Efecto de la Aplicación de Flavonoides en el Puerperio Bovino. - Chicaiza Iza, Gloria Noemi (2017)
The demand for food of animal origin has generated a challenge to improve the productivity of the farms; this way it has been a question reduce the age at first calving, the interval between deliveries and the number of services per pregnancy. Therefore, reproduction is a vital factor for good reproductive efficiency in dairy farms; Without however the involution of the reproductive apparatus of the bovine female is insufficient, taking several days and affecting its cyclicity; Therefore, to meet this goal, conception must occur before the 85th day postpartum. The objective of the present study was to evaluate the use of Flavonoids in the bovine puerperium to determine their effect on the involution of the reproductive tract in Holstein cows. Twenty-five cows between 2-5 years of age were postpartum, which were randomly assigned to the treatment group and to the control group. In the treatment group, a gynecological assessment was performed, determining the morphometry of the cervix, uterus and ovaries and percentage of involution, followed by uterine flavonoid infusion (purified micronized flavonoid fraction - diosmin® 400 mg) between 5 and 10 days Postpartum, and at 21 days the morphometric evaluation was again performed. In the control group to obtain the data, the evaluation was performed by ultrasonography between 5 and 10 days postpartum, as well as at 21 days postpartum to determine the morphometry of the reproductive system. These measurements were performed with an Aloka SSD-500 ultrasound with a 5 MHZ linear probe. For the interpretation of the results of the experiment we used the statistical analysis of Student to detect the existence of significant differences between the means of a given quantitative variable in two groups of related data. Thus, the results of the present study show that intrauterine application of 40% flavonoids (400 mg - diosmin) during bovine puerperium accelerated the involution of the reproductive tract. In addition, the involution of cervix, uterus and the ovarian size ratio of the treatment group was accelerated, which was very satisfactory with respect to the control group; The average at 21 days postpartum was estimated to be 97.3% with respect to the control group, which was 58%. Therefore, it is concluded that the involution of the reproductive system of the cow in the bovine puerperium was directly influenced by the flavonoids, indicating that the treatment with the flavonoids used in infusion to the uterus, favor the efficiency of the involution of the reproductive tract and its Annexes in high altitude environments in the Friesian Holstein breed.